Mixing efficiency in co-rotating batch mixer for preparation of NR/EPDM blends - Anont Chaisuriyathepkul (2018)
An in-house developed co-rotating batch mixer was used to prepare the blends of natural rubber (NR) and ethylene-propylene-diene terpolymer (EPDM) in the present work. Phase morphology and magnitude of dispersive mixing efficiency offered by the in-house developed co-rotating batch mixer and a conventional counter-rotating batch mixer were compared. It has been found that the co-rotating batch mixer equipped with the MX2 rotor configuration could improve the dispersive mixing efficiency of NR/EPDM blends considerably. A poor state-of-mix in blends, particularly at high fill factor, could be overcome by the utilization of MX2 rotor configuration where the extensional flow is probably facilitated in the converging zones. © 2011 Wiley Periodicals, Inc.